Tunnel film

CN119502511BActive Publication Date: 2026-10-27LUCKY FILM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411641674.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2026-10-27
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

现在市场上存在的温室大棚膜普遍存在防尘功能时效短影响棚膜使用寿命的问题,限制其在一些高端设施农业场景中的应用

Benefits of technology

[0027]本申请在两个表(即外层和内层)中加入了乙烯-甲基丙烯酸共聚物(Ethylene-Methacrylic Acid copolymer,简称EMA),EMA树脂较EVA极性更高,且耐水解性能好,用于外层可以增加该层的极性,实现与高分子永久型抗静电剂的相容性,避免因为高分子永久型抗静电剂与基体树脂不相容带来的表观发花、成型困难,抗静电剂发花等问题。此外,可以提升助剂相容性,保证外层的耐候性。用于内层可以提升表面能,实现与流滴消雾涂布液更好的附着性能。外层中,EMA的用量控制在10%~20%,内层中,EMA的用量控制在10%~20%,当用量低于10%时,不但对整体配方的极性提升有限,不能很好的与助剂和涂覆液匹配;当用量高于20%时,因为EMA粘结性能较强,会引起表层发粘,不利于生产和后期膜的开口。因此,用量控制在10%~20%合理。此外,由于EMA与聚丙烯的相容性不加,制膜容易出现表观“橘皮”等问题,所以,在体系中仍加入一定量的EVA来起到增容的作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138631810000151
    Figure BDA0005138631810000151
  • Figure BDA0005138631810000161
    Figure BDA0005138631810000161
  • Figure BDA0005138631810000162
    Figure BDA0005138631810000162
Patent Text Reader

Abstract

The application discloses a greenhouse film, which comprises an outer layer and an inner layer, and a core layer between the outer layer and the inner layer; the components of the outer layer include, with the mass fraction being 100, polyethylene I, 40-60 parts, polar resin I, 10-20 parts, polar resin II, 10-20 parts, dust-proof agent, 5-15 parts, anti-aging master batch, 5-20 parts, and ultraviolet absorption master batch, 1-7 parts. In addition, the components of the core layer include polyethylene I, polar resin II, heat preservation master batch and anti-aging master batch. The components of the inner layer include polyethylene I, polar resin I, polar resin II and anti-aging master batch. The polar resin I includes ethylene-methyl acrylic acid copolymer; the polar resin II includes ethylene-vinyl acetate copolymer; and the dust-proof agent includes a high-molecular permanent antistatic agent. The greenhouse film provided by the application is beneficial to realizing long-acting dust-proof function by optimizing the raw material components and the amount of each layer and meeting the above conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of agricultural film technology, specifically to greenhouse film. Background Technology

[0002] With the continuous development of facility agriculture, the requirements for agricultural greenhouse films are also increasing, and the greenhouse film market is gradually moving towards the high-end sector. Currently, most greenhouse films on the market have the problem of short-lasting dustproof function, which affects the lifespan of the film and limits its application in some high-end facility agriculture scenarios. Summary of the Invention

[0003] This application aims to at least partially solve one of the technical problems in the related art. To this end, one objective of this application is to propose a greenhouse film that, by optimizing the components and dosage of each layer, facilitates the achievement of a long-lasting dust-proof function.

[0004] The first aspect of this application discloses a greenhouse film. According to an embodiment of this application, the greenhouse film includes: an outer layer and an inner layer, and a core layer located between the outer layer and the inner layer;

[0005] The outer layer comprises the following components, in parts by mass of 100:

[0006] Polyethylene I, 40 parts to 60 parts

[0007] Polar resin I, 10 to 20 parts,

[0008] Polar resin II, 10 to 20 parts

[0009] Dust suppressant, 5 to 15 parts.

[0010] Aging-resistant masterbatch, 5 to 20 parts

[0011] Ultraviolet absorbing masterbatch, 1 part to 7 parts;

[0012] The core layer comprises, by weight parts per 100, the following components:

[0013] Polyethylene I, 40 parts to 60 parts

[0014] Polar resin II, 20 to 40 parts

[0015] Thermal insulation masterbatch, 1 part to 6 parts

[0016] Aging-resistant masterbatch, 5 to 20 parts;

[0017] Based on a mass fraction of 100, the components of the inner layer include:

[0018] Polyethylene I, 50 parts to 70 parts

[0019] Polar resin I, 10 to 20 parts,

[0020] Polar resin II, 10 to 20 parts

[0021] Aging-resistant masterbatch, 0 to 15 parts;

[0022] Polar resin I includes ethylene-methacrylic acid copolymer;

[0023] Polar resin II includes ethylene-vinyl acetate copolymer;

[0024] Dust-repellent agents include permanent polymeric antistatic agents.

[0025] The greenhouse film provided in this application has an outer layer serving as a dustproof and aging-resistant layer, a core layer serving as a heat-insulating and aging-resistant layer, and an inner layer serving as a coating liquid carrier layer. The raw material components and dosages of each layer meet the above conditions, which is conducive to achieving long-term dustproof function.

[0026] This application incorporates polar resins in each layer. The polar resin added to the core layer is ethylene-vinyl acetate copolymer (EVA). The introduction of polar groups effectively improves the compatibility of the resin system with anti-aging additives, allowing for increased additive dosage and further extending the lifespan of the greenhouse film. Furthermore, EVA has strong infrared absorption capabilities, which can improve the heat insulation performance of the greenhouse film. In the core layer, the amount of EVA is controlled between 20% and 40%. When the dosage is below 20%, the improvement in the overall polarity of the formulation is limited, and migration may occur when adding anti-aging additives. When the dosage is above 40%, firstly, it leads to a decrease in the overall tensile strength of the core layer, making it prone to greenhouse breakage in later use; secondly, EVA is more expensive than polyethylene, increasing costs. Therefore, controlling the dosage between 20% and 40% is reasonable. The amount of EVA used in the two surface layers should be controlled between 10% and 20%. When the amount is less than 10%, it not only has a limited effect on improving the polarity of the overall formulation, but also cannot act as a compatibilizer to adjust the compatibility between EMA and polyethylene I, which can easily cause orange peel texture. When the amount is more than 20%, firstly, it will lead to a decrease in the overall tensile strength of the core layer, making it easy to break in the later use; secondly, the price of EVA is higher than that of polyethylene, which will increase the cost. Therefore, it is reasonable to control the amount between 10% and 20%.

[0027] This application incorporates ethylene-methacrylic acid copolymer (EMA) into both layers (outer and inner layers). EMA resin has higher polarity and better hydrolysis resistance than EVA. Using it in the outer layer increases the polarity of this layer, achieving compatibility with the polymeric permanent antistatic agent and avoiding problems such as surface blooming, molding difficulties, and antistatic agent blooming caused by incompatibility between the polymeric permanent antistatic agent and the base resin. Furthermore, it improves the compatibility of additives and ensures the weather resistance of the outer layer. Using it in the inner layer increases surface energy, achieving better adhesion to the anti-drip and anti-fogging coating liquid. The amount of EMA in the outer layer is controlled at 10%–20%, and the amount in the inner layer is also controlled at 10%–20%. When the amount is below 10%, it not only has a limited effect on improving the overall polarity of the formulation but also fails to match well with additives and coating liquid; when the amount is above 20%, because of EMA's strong adhesive properties, it will cause the surface to become sticky, which is detrimental to production and subsequent film opening. Therefore, it is reasonable to control the dosage between 10% and 20%. In addition, since EMA and polypropylene are not compatible, problems such as "orange peel" appearance are prone to occur during film formation. Therefore, a certain amount of EVA is still added to the system to play a compatibilizing role.

[0028] This application incorporates a permanent polymeric antistatic agent as a dust-repellent agent in the outer layer. This permanent polymeric antistatic agent is a hydrophilic polymer. When blended with the polyethylene matrix, it exhibits strong molecular chain mobility, facilitating proton movement between molecules and enabling the conduction and release of static charges through ionic conductivity. Furthermore, it forms a fine, layered or ribbed distribution on the surface of the product, creating a conductive surface layer, while the central portion exhibits an almost spherical distribution, forming a so-called "core-shell structure," which serves as a pathway for static charge leakage. The permanent polymeric antistatic agent reduces the material's volume resistivity to achieve an antistatic effect, possessing permanent non-migratory properties, thus providing permanent antistatic and dust-repellent effects. The dosage of the outer layer of permanent polymer antistatic agent should be controlled between 5% and 15%. When the dosage is less than 5%, a continuous layered or ribbed distribution cannot be formed on the surface of the film, and a connected "core-shell structure" cannot be formed, so the charge cannot be smoothly discharged, affecting the antistatic effect. When the dosage is more than 15%, firstly, the excessive introduction of high-molecular materials that are different from the bulk phase will cause compatibility problems, and secondly, the price of permanent polymer antistatic agent is relatively expensive, which will increase the cost. Therefore, it is reasonable to control the dosage between 5% and 15%.

[0029] According to embodiments of this application, the methacrylic acid content in the ethylene-methacrylic acid copolymer is 12% to 29%; and / or, the vinyl acetate content in the ethylene-vinyl acetate copolymer is 8% to 18%.

[0030] According to embodiments of this application, the melting point of the dust suppressant is <150°C, and / or the viscosity of the dust suppressant is greater than the viscosity of the mixture of polyethylene I, polar resin I, and polar resin II.

[0031] According to the embodiments of this application, the melt index of polyethylene I is 0.2 g / 10 min to 1.0 g / 10 min.

[0032] According to embodiments of this application, the components of the aging-resistant masterbatch, based on 100 parts by weight, include:

[0033] Polyethylene II, 40-60 parts

[0034] Light stabilizer, 30 to 50 parts

[0035] Antioxidant, 0.5 to 5 parts;

[0036] And / or, based on 100 parts by weight, the components of the ultraviolet absorbing masterbatch include:

[0037] Polyethylene II, 70-90 parts

[0038] Ultraviolet absorber, 10 to 30 parts.

[0039] According to embodiments of this application, polyethylene II includes low-density polyethylene, and the melt index of polyethylene II is ≥2.0 g / 10 min.

[0040] According to embodiments of this application, the greenhouse film satisfies at least one of the following:

[0041] In aging-resistant masterbatches, light stabilizers include hindered amine light stabilizers;

[0042] In aging-resistant masterbatches, antioxidants include a combination of hindered phenols and phosphites;

[0043] In ultraviolet absorption masterbatch, the ultraviolet absorber includes at least one of salicylates, benzophenones, benzotriazoles, hindered amines, substituted acrylonitrile, and triazines.

[0044] According to embodiments of this application, the thermal insulation masterbatch includes hydrotalcite masterbatch.

[0045] According to an embodiment of this application, the greenhouse film further includes a coating layer that covers the inner surface.

[0046] According to embodiments of this application, the thickness ratio of the outer layer, core layer, and inner layer is (1-2):(3-8):1, and / or the total thickness of the greenhouse film is 130μm-170μm.

[0047] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation

[0048] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0049] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this application, unless otherwise stated, "multiple" means two or more.

[0050] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this application.

[0051] In this application, the terms "comprising" or "including" are open-ended expressions, meaning they include the content specified in this application but do not exclude other aspects.

[0052] With the continuous development of facility agriculture, the requirements for agricultural greenhouse films are also increasing, and the greenhouse film market is gradually moving towards the high-end sector. Currently, most greenhouse films on the market have the problem of short-lasting dustproof function, which affects the lifespan of the film and limits its application in some high-end facility agriculture scenarios.

[0053] Permanent polymeric antistatic agents have been used in other industries, but they suffer from poor compatibility with the base resin, which leads to reduced antistatic effect, difficulty in appearance and molding, and reduced durability, thus limiting their application in greenhouse film.

[0054] Therefore, the first aspect of the embodiments of this application provides a greenhouse film, comprising: an outer layer and an inner layer, and a core layer located between the outer layer and the inner layer;

[0055] The outer layer comprises the following components, in parts by mass of 100:

[0056] Polyethylene I, 40 parts to 60 parts

[0057] Polar resin I, 10 to 20 parts,

[0058] Polar resin II, 10 to 20 parts

[0059] Dust suppressant, 5 to 15 parts.

[0060] Aging-resistant masterbatch, 5 to 20 parts

[0061] Ultraviolet absorbing masterbatch, 1 part to 7 parts;

[0062] The core layer comprises, by weight parts per 100, the following components:

[0063] Polyethylene I, 40 parts to 60 parts

[0064] Polar resin II, 20 to 40 parts

[0065] Thermal insulation masterbatch, 1 part to 6 parts

[0066] Aging-resistant masterbatch, 5 to 20 parts;

[0067] Based on a mass fraction of 100, the components of the inner layer include:

[0068] Polyethylene I, 50 parts to 70 parts

[0069] Polar resin I, 10 to 20 parts,

[0070] Polar resin II, 10 to 20 parts

[0071] Aging-resistant masterbatch, 0 to 15 parts.

[0072] Polar resin I includes ethylene-methacrylic acid copolymer;

[0073] Polar resin II includes ethylene-vinyl acetate copolymer;

[0074] Dust-repellent agents include permanent polymeric antistatic agents.

[0075] The greenhouse film provided in this application embodiment has an outer layer serving as a dustproof and aging-resistant layer, a core layer serving as a heat-insulating and aging-resistant layer, and an inner layer serving as a coating liquid carrier layer. The raw material components and dosages of each layer meet the above conditions, which is conducive to achieving long-term dustproof function.

[0076] In the embodiments of this application, a polar resin is added to each layer.

[0077] The polar resin added to the core layer is ethylene-vinyl acetate copolymer (EVA). The introduction of polar groups effectively improves the compatibility of the resin system with anti-aging additives, allowing for increased additive dosage and further extending the lifespan of the greenhouse film. Furthermore, EVA has strong infrared absorption capabilities, which can improve the heat insulation performance of the greenhouse film. The amount of EVA in the core layer is controlled between 20% and 40%. When the dosage is below 20%, the improvement in the overall polarity of the formulation is limited, and migration may occur when adding anti-aging additives. When the dosage is above 40%, firstly, it leads to a decrease in the overall tensile strength of the core layer, making it prone to damage during later use; secondly, EVA is more expensive than polyethylene, increasing costs. Therefore, controlling the dosage between 20% and 40% is reasonable. The amount of EVA used in the two surface layers should be controlled between 10% and 20%. When the amount is less than 10%, it not only has a limited effect on improving the polarity of the overall formulation, but also cannot act as a compatibilizer to adjust the compatibility between EMA and polyethylene I, which can easily cause orange peel texture. When the amount is more than 20%, firstly, it will lead to a decrease in the overall tensile strength of the core layer, making it easy to break in the later use; secondly, the price of EVA is higher than that of polyethylene, which will increase the cost. Therefore, it is reasonable to control the amount between 10% and 20%.

[0078] In this embodiment, ethylene-methacrylic acid copolymer (EMA) is added to both layers (outer and inner layers). EMA resin has higher polarity than EVA and better hydrolysis resistance. Using it in the outer layer increases the polarity of the layer, achieving compatibility with the polymeric permanent antistatic agent and avoiding problems such as surface blooming, molding difficulties, and antistatic agent blooming caused by incompatibility between the polymeric permanent antistatic agent and the matrix resin. Furthermore, it improves the compatibility of additives and ensures the weather resistance of the outer layer. Using it in the inner layer increases surface energy, achieving better adhesion to the anti-drip and anti-fogging coating liquid. The amount of EMA in the outer layer is controlled at 10%–20%, and the amount in the inner layer is also controlled at 10%–20%. When the amount is below 10%, it not only has a limited effect on improving the overall polarity of the formulation but also cannot match well with additives and coating liquid; when the amount is above 20%, because of the strong adhesive properties of EMA, it will cause the surface to become sticky, which is not conducive to production and subsequent film opening. Therefore, it is reasonable to control the dosage between 10% and 20%. In addition, since EMA and polypropylene are not compatible, problems such as "orange peel" appearance are prone to occur during film formation. Therefore, a certain amount of EVA is still added to the system to play a compatibilizing role.

[0079] In specific examples, the amount of polar resin I added in the outer layer is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc. The amount of polar resin II added is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.

[0080] In specific examples, the amount of polar resin II added to the core layer is 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, etc.

[0081] In a specific example, the amount of polar resin I added in the inner layer is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc. The amount of polar resin II added is 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, etc.

[0082] In this embodiment, a permanent polymeric antistatic agent is added to the outer layer as a dust-repellent agent. This permanent polymeric antistatic agent is a hydrophilic polymer. When blended with the polyethylene matrix, it exhibits strong molecular chain mobility, facilitating proton movement between molecules and enabling the conduction and release of static charges through ionic conductivity. Furthermore, it forms a fine, layered or ribbed distribution on the surface of the product, creating a conductive surface layer, while the central portion exhibits an almost spherical distribution, forming a so-called "core-shell structure," which serves as a pathway for dissipating static charges. The permanent polymeric antistatic agent reduces the volume resistivity of the material to achieve an antistatic effect, possessing permanent non-migratory properties, thus providing permanent antistatic and dust-repellent effects.

[0083] The dosage of the outer layer of permanent polymer antistatic agent should be controlled between 5% and 15%. When the dosage is less than 5%, a continuous layered or ribbed distribution cannot be formed on the surface of the film, and a connected "core-shell structure" cannot be formed, so the charge cannot be smoothly discharged, affecting the antistatic effect. When the dosage is more than 15%, firstly, the excessive introduction of high-molecular materials that are different from the bulk phase will cause compatibility problems, and secondly, the price of permanent polymer antistatic agent is relatively expensive, which will increase the cost. Therefore, it is reasonable to control the dosage between 5% and 15%.

[0084] In specific examples, the amount of dust suppressant added is 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.

[0085] In some embodiments of this application, the raw material composition of the greenhouse film is as follows:

[0086] The outer layer comprises the following components, in parts by mass of 100:

[0087] Polyethylene I, 44 to 50 parts,

[0088] Polar resin I, 13 to 18 parts,

[0089] Polar resin II, 13 to 18 parts,

[0090] Dust suppressant, 8 to 12 parts

[0091] Aging-resistant masterbatch, 8 to 18 parts

[0092] Ultraviolet absorbing masterbatch, 2 to 5 parts;

[0093] The core layer comprises, by weight parts per 100, the following components:

[0094] Polyethylene I, 44-55 parts,

[0095] Polar resin II, 23-35 parts

[0096] Thermal insulation masterbatch, 2 to 5 parts

[0097] Aging-resistant masterbatch, 8 to 12 parts;

[0098] Based on a mass fraction of 100, the components of the inner layer include:

[0099] Polyethylene I, 55 parts to 65 parts,

[0100] Polar resin I, 12 to 18 parts,

[0101] Polar resin II, 12 to 18 parts,

[0102] Aging-resistant masterbatch, 5 to 10 parts.

[0103] In some embodiments of this application, the methacrylic acid content in the ethylene-methacrylic acid copolymer is 12% to 29%; and / or, the vinyl acetate content in the ethylene-vinyl acetate copolymer is 8% to 18%.

[0104] In the embodiments of this application, the content of vinyl acetate (VA) in the ethylene-vinyl acetate copolymer is 8% to 18%, which gives the greenhouse film excellent flexibility, impact resistance, elasticity and optical transparency.

[0105] In the embodiments of this application, the methacrylic acid (MA) content in the ethylene-methacrylic acid copolymer is 12% to 29%. If the MA content is too low, the polarity of the material will be too low, making it difficult to guarantee compatibility with polymeric permanent antistatic agents and anti-aging additives. However, if the MA content is too high, it will affect the material's flowability and plasticity, thereby affecting the moldability during processing and the final appearance of the product. In specific examples, the methacrylic acid content is 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, etc.

[0106] In some embodiments of this application, the ethylene-vinyl acetate copolymer includes at least one of the following: FL00014 manufactured by ExxonMobil, FL00018 manufactured by ExxonMobil, V4110F manufactured by Yangba, E120A manufactured by Hanwha, and 14-2 manufactured by Beijing Organic Chemical.

[0107] In some embodiments of this application, the ethylene-methacrylic acid copolymer includes at least one of the grades 24MA005 and 18MA03 produced by Arkema, France.

[0108] In some embodiments of this application, the melting point of the dust suppressant is <150°C, and / or the viscosity of the dust suppressant is greater than the viscosity of the mixture of polyethylene I, polar resin I and polar resin II.

[0109] In the embodiments of this application, the degree of dispersion and state of the antistatic agent determine the antistatic effect.

[0110] In this embodiment, a polyamide-polyether type polymeric antistatic agent with a melting point of <150℃ is specifically used. This type of antistatic agent has little impact on the performance of the matrix material, and when used in conjunction with a polar resin at the processing temperature of polyethylene, it can achieve good compatibility with polyethylene.

[0111] In this embodiment, the viscosity of the polymeric permanent antistatic agent is controlled to be greater than the viscosity of the mixture of polyethylene, polar resin I, and polar resin II. This viscosity difference allows the low-viscosity matrix resin to more easily form a continuous phase and coat the surface of the higher-viscosity antistatic agent. Furthermore, by controlling the viscosity, a small amount of antistatic agent can exist as a continuous dispersed phase within a large amount of matrix resin, forming a network and fixing it during the molding process, thus improving the antistatic effect.

[0112] Furthermore, permanent polymeric antistatic agents include polyamide-polyether type polymeric antistatic agents.

[0113] Furthermore, permanent polymeric antistatic agents include antistatic agents produced by Sanyo Chemical or Croda.

[0114] In some embodiments of this application, the melt index of polyethylene I is 0.2 g / 10 min to 1.0 g / 10 min. In specific examples, the melt index of polyethylene I is 0.2 g / 10 min, 0.3 g / 10 min, 0.4 g / 10 min, 0.5 g / 10 min, 0.6 g / 10 min, 0.7 g / 10 min, 0.8 g / 10 min, 0.9 g / 10 min, 1 g / 10 min, etc.

[0115] Furthermore, the polyethylene I is metallocene linear low-density polyethylene (mLLDPE), and the melt index of the metallocene polyethylene is below 1.0 g / 10 min.

[0116] In this embodiment, metallocene linear low-density polyethylene (metallocene LLDPE) has a high relative molecular mass and a dense molecular distribution, which makes it better resistant to fracture and impact when subjected to external forces, maintaining the integrity and functionality of the material. The transparency of polyethylene polymers increases with increasing molecular weight. When the crystallinity is constant, the transparency of metallocene LLDPE is better than that of traditional polyethylene, which improves the light transmittance, strength, and rub resistance of the greenhouse film, effectively preventing the "backsheet effect" of the greenhouse film.

[0117] Furthermore, metallocene linear low-density polyethylene includes at least one of the grades 2010MA, 2005MC, XP6056 ML, and XP6026 ML manufactured by ExxonMobil.

[0118] In some embodiments of this application,

[0119] The components of the aging-resistant masterbatch, calculated in parts by weight of 100, include:

[0120] Polyethylene II, 40-60 parts

[0121] Light stabilizer, 30 to 50 parts

[0122] Antioxidant, 0.5 to 5 parts;

[0123] And / or, based on 100 parts by weight, the components of the ultraviolet absorbing masterbatch include:

[0124] Polyethylene II, 70-90 parts

[0125] Ultraviolet absorber, 10 to 30 parts.

[0126] In this embodiment, aging-resistant masterbatch is added to the outer layer, core layer and inner layer. The composition and content of the aging-resistant masterbatch meet the above conditions, which is beneficial to improving the overall aging resistance of the greenhouse film.

[0127] In this embodiment, ultraviolet (UV) absorbing masterbatch is added to the outer layer. The composition and content of the UV absorbing masterbatch meet the above conditions, which helps to improve the radiation resistance and aging resistance of the greenhouse film. Ultraviolet radiation is the root cause of greenhouse film degradation. UV absorbers can eliminate or partially eliminate UV radiation. Furthermore, several UV absorbers with different central absorption wavelengths can be used in combination to better control the cutoff of ultraviolet light by the product.

[0128] In some embodiments of this application, polyethylene II includes low-density polyethylene, and the melt index of polyethylene II is >2.0 g / 10 min.

[0129] Furthermore, the melt index of polyethylene II is 2.0 g / 10 min to 4.0 g / 10 min. A melt index greater than 2.0 g / 10 min indicates good flowability of polyethylene, making molding and processing easier during the preparation of aging-resistant masterbatches or UV-absorbing masterbatches. However, if the melt index is too high, the flowability of the aging-resistant masterbatch or UV-absorbing masterbatch will differ significantly from that of the greenhouse film base material, resulting in a flowability mismatch during film formation and causing poor film appearance.

[0130] In some embodiments of this application, at least one of the following is satisfied:

[0131] In aging-resistant masterbatches, light stabilizers include hindered amine light stabilizers;

[0132] In aging-resistant masterbatches, antioxidants include a combination of hindered phenols and phosphites;

[0133] In ultraviolet absorption masterbatch, the ultraviolet absorber includes at least one of salicylates, benzophenones, benzotriazoles, hindered amines, substituted acrylonitrile, and triazines.

[0134] In this embodiment, hindered amine light stabilizers, hindered phenolic and phosphite antioxidants are added to the aging-resistant masterbatch. After absorbing light energy in an aerobic state, the hindered amine light stabilizer can be converted into nitroxide radicals (NO·). These nitroxide radicals can capture alkyl reactive radicals generated during the photo-oxidative degradation of polymer materials and decompose their peroxides. A more preferred approach is to add a basic, low-NOR type light stabilizer. The introduction of alkoxy groups reduces the electron cloud density of reactive nitrogen and can directly form nitroxide radicals (NO·), avoiding the process of traditional hindered amines generating nitroxide radicals being delayed or prevented by chemical substances. This approach has excellent application effects in high-concentration pesticide environments (such as sulfur-containing pesticides).

[0135] In this embodiment, an antioxidant is added to the aging-resistant masterbatch. The antioxidant plays the role of capturing free radicals and peroxides generated during production, processing or thermo-oxidative decomposition.

[0136] Furthermore, in the embodiments of this application, the synergistic effect of the antioxidant, hindered amine light stabilizer, and ultraviolet absorber demonstrates superior weather resistance compared to the application of any one or two of them alone. Experiments have confirmed that their combination does not inhibit each other. Through the combined use of the aging-resistant masterbatch and the ultraviolet-absorbing masterbatch, the long-lasting dustproof greenhouse film can achieve a service life of 8 years.

[0137] In some embodiments of this application, the thermal insulation masterbatch includes hydrotalcite masterbatch.

[0138] In this embodiment, hydrotalcite masterbatch is used as the thermal insulation masterbatch, and the hydrotalcite is at 1360cm. -1 It has a strong absorption spectrum at 650 cm⁻¹ -1 ~1000cm -1 It has a strong vibrational absorption spectral band, which falls within the peak wavelength range for heat dissipation of the greenhouse film. Adding hydrotalcite can provide excellent heat preservation. Furthermore, the addition of hydrotalcite masterbatch increases crystallization centers in the resin, acting as a nucleating agent, increasing the number of crystals and reducing their size. This reduces light refraction and makes the film more transparent.

[0139] In some embodiments of this application, the content of hydrotalcite in the hydrotalcite masterbatch is 20% to 50%.

[0140] In this embodiment, the hydrotalcite content in the masterbatch is 20%–50%. This concentration of masterbatch has the most mature preparation process, and there are many commercially available products. The raw materials are simple, readily available, and relatively economical. Specific examples show hydrotalcite content in the masterbatch of 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, 20%, etc.

[0141] Furthermore, the hydrotalcite masterbatch includes hydrotalcite masterbatch produced by Kyowa Chemicals or Sakai Chemicals.

[0142] In some embodiments of this application, the greenhouse film further includes a coating layer that covers the inner surface.

[0143] In this embodiment, the coating layer can be prepared using a commercially available coating solution. Further, the dry matter content of the dried coating layer is >0.22 g / m³. 2 .

[0144] In some embodiments of this application, the thickness ratio of the outer layer, core layer and inner layer is (1-2):(3-8):1, and / or the total thickness of the greenhouse film is 130μm-170μm.

[0145] In this embodiment, the thickness ratio of the outer layer, core layer, and inner layer meets the above conditions, which is beneficial to the overall performance of the greenhouse film. An ultraviolet absorber is added to the outer layer; if the thickness is too low, it will not effectively block ultraviolet rays, affecting the lifespan of the greenhouse film. If the thickness is too high, the cost will increase due to the high price of the ultraviolet absorber. If the thickness of the inner layer is too low, it will affect the adhesion of the coating liquid and limit processing equipment; if the thickness is too high, the cost will also increase due to the high price of polar EMA resin. Specific examples show that the thickness ratio of the outer layer, core layer, and inner layer is 1:3:1, 1:4:1, 1:5:1, 1:6:1, 1:7:1, 1:8:1, 2:3:1, 2:4:1, 2:5:1, 2:6:1, 2:7:1, 2:8:1, etc.

[0146] In this embodiment, the total thickness of the greenhouse film is limited to 130μm to 170μm. This thickness is beneficial for ensuring the mechanical properties and light transmittance of the greenhouse film. In specific examples, the total thickness of the greenhouse film is limited to 130μm, 131μm, 132μm, 133μm, 134μm, 135μm, 136μm, 137μm, 138μm, 139μm, 140μm, 41μm, 142μm, 143μm, 144μm, 145μm, 146μm, 147μm, 148μm, 149μm, 150μm, etc.

[0147] The second aspect of this application provides a method for preparing greenhouse film, comprising the steps of:

[0148] The materials of the outer layer, core layer and inner layer are mixed and stirred separately, and then added to a three-layer co-extrusion extruder. After melting, plasticizing and blow molding, cooling and shaping, traction, corona treatment, coating liquid impregnation, drying and folding, the above-mentioned greenhouse film is obtained.

[0149] The method for preparing the greenhouse film in this application embodiment is scientifically sound, produces stable and reliable quality, and is simple and easy to operate. The greenhouse film prepared in this application embodiment has an outer layer serving as a dustproof and aging-resistant layer, a core layer serving as a heat-insulating and aging-resistant layer, and an inner layer serving as a coating liquid carrier layer. The raw material components and dosages of each layer meet the above conditions, which is beneficial for achieving long-term dustproof function. The multi-layer greenhouse film provided in this application embodiment uses a specially structured permanent polymeric antistatic agent in the outer layer. Combined with the material design of the matrix resin, this agent can be dispersed in a special form within the outer film. Through ion conduction, it conducts and releases the generated static electricity, eliminating static charges inside and on the surface of the film. Furthermore, the permanent polymeric antistatic agent does not migrate and is less affected by environmental humidity, which is beneficial for achieving a long-term dustproof effect.

[0150] In some embodiments of this application, the control parameters in the method for preparing the greenhouse film include:

[0151] The extruder temperature is 150℃~200℃, and the die temperature is 190℃~215℃;

[0152] The drying temperature is 85℃~102℃;

[0153] The blow-up ratio for blow molding is 1.5 to 2.5.

[0154] In some embodiments of this application, a method for preparing an aging-resistant masterbatch is provided, comprising the steps of:

[0155] Polyethylene II, light stabilizer, and antioxidant are mixed at high speed in a high-speed mixer according to a certain ratio, then added to an internal mixer for kneading, and then fed into a twin-screw extruder by a feeder. After being pelletized by water ring or underwater, aging-resistant masterbatch is obtained.

[0156] In some embodiments of this application, a method for preparing ultraviolet absorbing masterbatch is provided, comprising the steps of:

[0157] Polyethylene II and ultraviolet absorber are mixed at high speed in a high-speed mixer according to a certain ratio, then added to an internal mixer for kneading, and then fed into a twin-screw extruder by a feeder. After being pelletized by water ring or underwater, ultraviolet absorbing masterbatch is obtained.

[0158] The following will explain the solution of this application with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0159] Example 1

[0160] Greenhouse film

[0161] The greenhouse film consists of an outer layer, a core layer, an inner layer, and a coating layer. The components of each layer are expressed in parts by weight, and the specific components of each layer are shown below:

[0162] 1. Outer layer

[0163] Polyethylene I: 60 parts, Exxon's XP 6056ML.

[0164] Polar resin I: 10 parts, ethylene-methacrylic acid copolymer, methacrylic acid content is 18%, Arkema 18MA02.

[0165] Polar resin II: 10 parts, ethylene-vinyl acetate copolymer, with a vinyl acetate content of 18% Hanwha Total E180L.

[0166] Dust suppressant: 10 parts, Croda FSTAT2.

[0167] Aging-resistant masterbatch: 8 parts.

[0168] Ultraviolet absorbing masterbatch: 2 parts.

[0169] 2. Core layer

[0170] Polyethylene I: 60 parts, Exxon's XP 6056ML.

[0171] Polar resin II: 20 parts, ethylene-vinyl acetate copolymer, vinyl acetate content is 18%, Hanwha Total E180L.

[0172] Thermal insulation masterbatch: 5 parts, Shandong Kuanli's 36% concentration hydrotalcite masterbatch.

[0173] Aging-resistant masterbatch: 15 parts.

[0174] 3. Inner layer

[0175] Polyethylene I: 70 parts, Exxon's XP 6056ML.

[0176] Polar resin I: 10 parts, ethylene-methacrylic acid copolymer, methacrylic acid content is 18%, Arkema 18MA02.

[0177] Polar resin II: 15 parts, ethylene-vinyl acetate copolymer, vinyl acetate content is 18%, Hanwha Total E180L.

[0178] Aging-resistant masterbatch: 5 parts.

[0179] 4. Preparation of greenhouse film

[0180] The outer, core, and inner layers are mixed and stirred evenly, then fed into a three-layer co-extrusion extruder. After melt plasticizing and blow molding, cooling and shaping, traction, corona treatment, coating impregnation, drying, and folding, the finished greenhouse film is obtained. The resulting product has a thickness of 150 μm; the layer thickness ratio of the outer, core, and inner layers is 1.5:5:1; and the blow-up ratio is 2.2. The extruder temperature is 190℃, the die temperature is 210℃, and the oven temperature is 95℃.

[0181] The components and preparation methods of the aging-resistant masterbatch, ultraviolet-absorbing masterbatch, and coating layer are as follows:

[0182] (1) Aging-resistant masterbatch:

[0183] The raw material composition of the aging-resistant masterbatch, by weight, is as follows: 55 parts polyethylene II, 42 parts light stabilizer, and 3 parts antioxidant. Among them, polyethylene II is low-density polyethylene powder with a melt index of 3.5 g / 10 min; the stabilizer is Cytec 3529; and the antioxidant is Changchun Chemical 1010.

[0184] The preparation method of the aging-resistant masterbatch is as follows: 55 parts of polyethylene II, 42 parts of light stabilizer and 3 parts of antioxidant are accurately measured and added to the internal mixer for kneading and plasticizing. Then, the mixture is fed into a single screw extruder granulator through an open mill, hot-cut into pellets, and then air-cooled and dried to obtain the aging-resistant masterbatch for later use.

[0185] The internal mixer temperature is 135℃, the plasticizing time is 20min, and the temperature of each section of the single screw is 140℃~160℃ (of which, zone 1 is 160℃, zone 2 is 160℃, and zone 3 is 140℃).

[0186] (2) Ultraviolet Absorbing Masterbatch:

[0187] The raw material composition of the UV absorbing masterbatch, by weight, is as follows: 80 parts of polyethylene II and 20 parts of UV absorber. The polyethylene II is low-density polyethylene powder with a melt flow index of 3.5 g / 10 min; the UV absorber is BASF 1577.

[0188] The preparation method of ultraviolet absorbing masterbatch is as follows: 80 parts of polyethylene II and 20 parts of ultraviolet absorber are accurately metered and added to a mixer for kneading and plasticizing. Then, the mixture is fed into a single-screw extruder granulator through an open mill, hot-cut into pellets, and then air-cooled and dried to obtain ultraviolet absorbing masterbatch for later use.

[0189] The internal mixer temperature is 135℃, the plasticizing time is 20min, and the temperature of each section of the single screw is 140℃~160℃ (of which, zone 1 is 160℃, zone 2 is 160℃, and zone 3 is 140℃).

[0190] (3) Coating layer:

[0191] The coating material composition is as follows: 9% coating solution stock solution and 91% deionized water. Among them, the coating solution stock solution is TG-150, manufactured by Takemoto Oils & Fats Co., Ltd. of Japan.

[0192] The coating preparation method is as follows: Weigh the prepared coating solution stock solution and add it to a stainless steel tank. Then, add deionized water according to the specified ratio, stir well, let it stand for 20 minutes, and then pump it into a hanging tank for later use. The dry matter content of the coating layer is 0.25 g / m³. 2 .

[0193] Examples 2-4

[0194] The greenhouse films provided in Examples 2-4 are the same as those in Example 1, except that the component dosages have been changed, as shown in Tables 1-3.

[0195] Comparative Examples 1-6

[0196] The greenhouse films provided in Comparative Examples 1-6 are as shown in Example 1, except that the components and dosages have been changed, as shown in Tables 1-3.

[0197] In Comparative Example 5, the common dust suppressant added to the outer layer formulation is a commercially available common dust suppressant masterbatch, such as EFT997 produced by Tianjin Riken Co., Ltd. or BE-10F produced by Jilin Baien Plastic Technology Co., Ltd. The common dust suppressant masterbatch used in Comparative Example 5 is EFT997 produced by Tianjin Riken Co., Ltd.

[0198] Comparative Example 6 introduced 10 parts by weight of commercially available internal additive anti-drip and anti-fogging masterbatch into the inner layer formulation, such as the grades KF-650 and CF-702 produced by Tianjin Riken Co., Ltd. This comparative example uses grade KF-650.

[0199] Table 1. Raw material composition of the outer layer

[0200]

[0201] Table 2. Raw material composition of the core layer

[0202]

[0203] Table 2. Raw material composition of the inner layer

[0204]

[0205] Performance testing

[0206] I. Testing Method:

[0207] 1. Surface resistivity:

[0208] (1) Outer appearance: visually.

[0209] (2) Initial resistance: Tested based on GB / T 1410-2006.

[0210] (3) 40℃ water boiling test: Place the sample in a 40℃ water bath and age for 24 hours. Then remove it and air dry at room temperature. Finally, measure the surface resistance of the sample according to GB / T 1410-2006.

[0211] (4) 60℃ migration test: Place the sample in a 60℃ oven and leave it for 8 days. Then take it out and measure the surface resistance of the sample according to GB / T1410-2006.

[0212] (5) Room temperature water flushing test: In a room temperature environment, fix the sample 10cm away from the shower head in the bathroom, then continuously flush it with tap water for 24h, and let it air dry at room temperature. Measure the surface resistance of the sample according to GB / T 1410-2006.

[0213] 2. Anti-drip and anti-fogging performance water bath test: The anti-drip and anti-fogging performance is tested according to the anti-drip performance test requirements in section 4.6 of the industry standard "Coated Persistent Anti-Drip Polyethylene Greenhouse Film" QB / T4475-2013. The test time is 60 days for 3-year film, 90 days for 5-year film, 105 days for 6-year film, 120 days for 7-year film, and 135 days for 8-year film.

[0214] 3. Other:

[0215] (1) Infrared transmittance: Tested in accordance with T / CPIA 0015-2019.

[0216] (2) UV radiation resistance: Tested in accordance with T / CPIA 0015-2019.

[0217] II. Test Results:

[0218] Table 4. Surface resistance test results of the samples provided in the examples and comparative examples.

[0219]

[0220] The test results reflected in Table 4 show that the surface resistivity of the samples provided in Examples 1 to 4 is all above 10. 11The presence of these layers indicates that the greenhouse film is more conductive, effectively dissipating static electricity and reducing its accumulation. This reduces the likelihood of electrostatic discharge, preventing various problems caused by static electricity, such as dust accumulation. Furthermore, its stability after various aging processes demonstrates the excellent antistatic performance of the overall formulation using a high-polymer permanent antistatic agent on the outer layer, providing long-lasting dustproof effects. Comparative Examples 1, 3, and 5-6, lacking or containing only a small amount of high-polymer permanent antistatic agent, failed to achieve satisfactory antistatic effects. Comparative Examples 2 and 4 exhibited surface problems due to an unsuitable resin system.

[0221] Table 5. Results of water bath test on the anti-drip and anti-fogging performance of the samples provided in the examples and comparative examples.

[0222]

[0223] The test results reflected in Table 5 show that the samples provided in Examples 1-4, with the overall introduction of polar resin and the greenhouse film prepared by the coating process, have a long-lasting anti-drip and anti-fogging function that can be synchronized with the service life of the greenhouse film. In Comparative Examples 1-5, the proportion of polar resin used was inappropriate; in Comparative Example 6, due to the use of an internally added anti-drip and anti-fogging agent, the anti-drip and anti-fogging duration was less than 6-7 years.

[0224] Table 6 Performance test results of the samples provided in the examples and comparative examples.

[0225]

[0226] The test results reflected in Table 6 show that the infrared transmittance and UV irradiation resistance of the samples provided in Examples 1-4 are all better than those of Comparative Examples 1-6, reflecting a significant improvement in their thermal insulation performance and aging resistance.

[0227] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A greenhouse film, characterized in that, include: Outer layer and inner layer, and core layer located between the outer layer and the inner layer; The outer layer comprises, in parts by mass of 100, the following components: Polyethylene I, 40 parts to 60 parts Polar resin I, 10 to 20 parts, Polar resin II, 10 to 20 parts, Dust suppressant, 5 to 15 parts Aging-resistant masterbatch, 5 parts to 20 parts Ultraviolet absorbing masterbatch, 1 to 7 parts; The core layer comprises, in parts by weight of 100, the following components: Polyethylene I, 40 parts to 60 parts Polar resin II, 20 to 40 parts, Thermal insulation masterbatch, 1 part to 6 parts Aging-resistant masterbatch, 5 to 20 parts; The components of the inner layer, in parts by weight of 100, include: Polyethylene I, 50-70 parts Polar resin I, 10 to 20 parts, Polar resin II, 10 to 20 parts, Aging-resistant masterbatch, 0 to 15 parts; The polar resin I includes an ethylene-methacrylic acid copolymer; The polar resin II includes an ethylene-vinyl acetate copolymer; The polyethylene I is metallocene linear low-density polyethylene (mLLDPE); In the ethylene-methacrylic acid copolymer, the content of methacrylic acid is 12%~29%; In the ethylene-vinyl acetate copolymer, the content of vinyl acetate is 8% to 18%; The dust suppressant has a melting point of <150 ℃ and is a polyamide polyether type polymeric antistatic agent with a viscosity greater than that of the mixture of polyethylene I, polar resin I and polar resin II. The melt index of the polyethylene I is 0.2 g / 10min to 1.0 g / 10min.

2. The greenhouse film according to claim 1, characterized in that, The components of the aging-resistant masterbatch, based on 100 parts by weight, include: Polyethylene II, 40-60 parts Light stabilizer, 30-50 parts Antioxidant, 0.5 to 5 parts; The components of the ultraviolet absorbing masterbatch, calculated in parts by weight of 100, include: Polyethylene II, 70-90 parts Ultraviolet absorber, 10 to 30 parts.

3. The greenhouse film according to claim 2, characterized in that, The polyethylene II includes low-density polyethylene, and the melt flow index of the polyethylene II is ≥2.0 g / 10min.

4. The greenhouse film according to claim 2, characterized in that, Meet at least one of the following: In the aging-resistant masterbatch, the light stabilizer includes hindered amine light stabilizers; In the aging-resistant masterbatch, the antioxidant includes a composite antioxidant of hindered phenols and phosphites; In the ultraviolet absorbing masterbatch, the ultraviolet absorber includes at least one of salicylate ultraviolet absorbers, benzophenone ultraviolet absorbers, benzotriazole ultraviolet absorbers, substituted acrylonitrile ultraviolet absorbers, and triazine ultraviolet absorbers.

5. The greenhouse film according to claim 1, characterized in that, The thermal insulation masterbatch includes hydrotalcite masterbatch.

6. The greenhouse film according to claim 1, characterized in that, It also includes a coating layer that covers the surface of the inner layer.

7. The greenhouse film according to any one of claims 1 to 6, characterized in that, The thickness ratio of the outer layer, the core layer and the inner layer is (1~2):(3~8):1, and / or the total thickness of the greenhouse film is 130 μm~170 μm.

Citation Information

Patent Citations

  • Coating type dimming dustproof high-heat-preservation long-acting dripping fog dissipation greenhouse film and preparation method thereof

    CN112840915A

  • Antistatic polypropylene coating material and preparation method thereof

    CN115058155A

  • Antistatic polyethylene composition and product thereof, and preparation method thereof

    CN118652490A